Clinical course of avian influenza A(H5N1) in patients at the Persahabatan Hospital, Jakarta, Indonesia, 2005-2008. - Soepandi, P; Burhan, E; Mangunnegoro, H; Nawas, A; Aditama, T; Partakusuma, L; Isbaniah, F; Ikhsan, M; Swidarmoko, B; Sutiyoso, A; Malik, S; Benamore, R; et al. (2010)
BACKGROUND: Limited understanding of the presentation and course of influenza A(H5N1) infection in humans hinders evidence-based management. METHODS: We reviewed the case records of patients admitted to the Persahabatan Hospital (RSP), Jakarta, Indonesia, with influenza A(H5N1) confirmed by real-time polymerase chain reaction. RESULTS: Twenty-two previously well patients, aged 3 to 47 years (median 24.5 years), were identified. All attended a clinic or hospital after a median of 2 days of illness (range 0-7). Times to first dose of oseltamivir (three died before receiving oseltamivir) were 2 to 12 days (median 7 days), administered mostly (n = 15) at RSP. Nineteen patients required mechanical ventilation. Deaths numbered 18 (case fatality = 82%) occurring within hours to 6 days of RSP admission, corresponding to 6 to 16 days of illness. Admission hyperglycemia ( >or= 140 mg/dL), unrelated to steroids or known underlying diabetes mellitus, and elevated D-dimer levels (0.81-5.2 mg/L, upper limit of normal < 0.5 mg/L) were present in 14/21 (67%) and 20/21 (95%) patients, respectively. Fibrinogen concentrations were mostly low/normal at 129.9 to 517.9 mg/dL (median 241.1, normal 200-400 mg/dL), whereas C-reactive protein (9/11) and ferritin (6/8) levels were increased. Risk factors for death (univariate analysis) included: (1) increased D-dimers, (2) hyperglycema, (3) increased urea, (4) more extensive chest radiograph shadowing, and (5) lower admission oxygen saturation. CONCLUSIONS: Early diagnosis and effective treatment of human influenza A(H5N1) infection remains challenging. Most patients were referred late with advanced disease. Oseltamivir had limited clinical impact. Elevated D-dimer levels, consistent with fibrinolysis, and hyperglycemia warrant more research to determine their underlying mechanisms and optimal treatment.